Stance instability in spinocerebellar ataxia type 6. Issue 4 (9th November 2012) - Bunn, Lisa M.; Marsden, Jonathan F.; Giunti, Paola; Day, Brian L.
<x xml:space="preserve">Abstract</x> Balance impairment is a principal symptom of cerebellar disease, but is poorly understood partly because subjects with heterogenous cerebellar and extracerebellar lesions have often been studied. Spinocerebellar ataxia type 6 (SCA6) provides an opportunity to understand balance dysfunction associated with a relatively homogenous cerebellar lesion. This study investigated stance instability in SCA6 and how it is affected by varying stance width. Body sway, as well as its directional preponderance and distribution across joints, was measured three‐dimensionally in 17 SCA6 and 17 matched healthy control subjects. Subjects stood for 40 seconds on a stable surface with their eyes open and feet positioned at various stance widths (32, 16, 8, 4, and 0 cm). SCA6 subjects swayed faster than controls at every stance width. Decreasing the stance width produced a disproportionate increase in sway speed in SCA6 subjects, compared to controls. Directional preponderance of sway was dependent on stance width, but did not differ between groups. Joint instability was increased by reducing stance width in both groups, but there was greater instability of the ankle joint in the roll plane in the SCA6 group. Measures of global instability correlated strongly with disease severity measured with the Scale for the Assessment and Rating of Ataxia (r = 0.79). The sway characteristics suggest a disruption of sensorimotor processing for balance control in SCA6. The correlation with disease severity implies that balance impairment is a feature of progression of SCA6 clinical syndrome. With stance width standardized, the instability measures employed could provide sensitive, continuous outcome measures of longitudinal or therapeutic change. © 2012 Movement Disorder Society